2018
DOI: 10.1159/000493460
|View full text |Cite
|
Sign up to set email alerts
|

The in Vitro Effect of Polyvinylpyrrolidone and Citrate Coated Silver Nanoparticles on Erythrocytic Oxidative Damage and Eryptosis

Abstract: Background/Aims: Silver nanoparticles (AgNPs) are increasingly used as antimicrobial agents and drug carriers in various biomedical fields. AgNPs can encounter erythrocytes either directly following intravenous injection, or indirectly via translocation from the site of administration. However, information regarding the pathophysiological effects and possible mechanism of action of AgNPs on the erythrocytes are still inadequately studied. Thus, the aim of our study was to investigate the mechanism underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 48 publications
3
26
1
Order By: Relevance
“…Figure 22d showed the internalized AgNPs in RBCs, leading to membrane injury, lipid peroxidation, and eventual hemolysis. Very recently, Ferdous et al studied the interactions of PVP and citrate coated AgNPs (10 nm) of various concentrations (2.5, 10, 40 µg/mL) with murine RBCs [214]. AgNPs induced significant dose-dependent hemolysis, resulting from cellular uptake of AgNPs and oxidative stress generation.…”
Section: In Vitro Cell Cultivationmentioning
confidence: 99%
“…Figure 22d showed the internalized AgNPs in RBCs, leading to membrane injury, lipid peroxidation, and eventual hemolysis. Very recently, Ferdous et al studied the interactions of PVP and citrate coated AgNPs (10 nm) of various concentrations (2.5, 10, 40 µg/mL) with murine RBCs [214]. AgNPs induced significant dose-dependent hemolysis, resulting from cellular uptake of AgNPs and oxidative stress generation.…”
Section: In Vitro Cell Cultivationmentioning
confidence: 99%
“…In vitro cytotoxicity studies are often used to characterize the biological response to AgNPs, and the results of these studies may be used to identify hazards associated with exposure to AgNPs. Some important studies that have shown the toxic effects of AgNPs on different cell lines, including macrophages (RAW 264.7), including bronchial epithelial cells (BEAS-2B), alveolar epithelial cells (A549), hepatocytes (C3A, HepG2), colon cells (Caco2), skin keratinocytes (HaCaT), human epidermal keratinocytes (HEKs), erythrocytes, neuroblastoma cells, embryonic kidney cells (HEK293T), porcine kidney cells (Pk 15), monocytic cells (THP-1), and stem cells [20,[108][109][110][111][112][113][114][115][116][117], are discussed below.…”
Section: In Vitro Effectsmentioning
confidence: 99%
“…Studies that used human erythrocytes have investigated the effects of AgNPs on hemolysis, morphology, and their uptake [132,134]. In our recent in vitro study, we assessed the effect of the coating and dose of AgNPs on oxidative damage and eryptosis on mice erythrocytes [111]. Both PVP and CT-AgNPs induced oxidative stress and increased cytosolic calcium, annexin V binding, and calpain activity.…”
Section: In Vitro Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] The characteristic properties of AgNPs, including size, surface area, coating, surface chemistry, and charge of the NPs, play a significant role in their toxicity and hemolytic activity. [ 7,9–11 ]…”
Section: Introductionmentioning
confidence: 99%